Pengaruh Iklan Media Sosial Dan Word Of Mouth Terhadap Keputusan Pembelian - Jecky Jecky; Rezi Erdiansyah (Prologia, 2021)
This study aims to determine the effect of advertising on social media and word of mouth on purchasing decisions using a quantitative descriptive approach. Researchers took samples using google form with a total of 145 respondents who were distributed via social media. Data analysis was conducted by researchers using the program of statistical product and service solutions (SPSS) version 15. Based on the results of the research that has been obtained and has been explained by the author regarding advertising on social media and word of mouth on purchasing decisions. It is known that the coefficient of determination in the R Square table is 0.475, indicating that 47.5% of purchasing decisions are influenced by advertising on social media and the word of mouth. It is known that the correlation coefficient value of 0.60-0.799 means that advertising on social media and Word of Mouth has a strong relationship to purchasing decisions. then from the results obtained, the authors can provide several conclusions. The conclusion is that advertising on social media and word of mouth has a positive and significant effect on purchasing decisions.Penelitian ini bertujuan untuk mengetahui pengaruh Iklan Media Sosial dan word of mouth  terhadap Keputusan Pembelian dengan menggunakan pendekatan deskriptif kuantitatif. Peneliti mengambil sampel dengan menggunakan google form dengan total 145 responden yang di sebarkan melalui media sosial. Analisis data yang dilakukan peneliti menggunakan program statistical product and service solutions (SPSS) versi 15. Berdasarkan hasil penelitian yang telah diperoleh dan telah dijelaskan oleh penulis mengenai Iklan Media Sosial dan word of mouth terhadap keputusan pembelian. Diketahui bahwa nilai koefisien determinasi pada tabel R Square sebesar 0.475 menunjukkan bahwa 47,5% keputusan pembelian dipengaruhi oleh Iklan Media Sosial dan Word of Mouth. Diketahui bahwa nilai koefiesien korelasi 0,60-0,799 artinya Iklan Media Sosial dan Word of Mouth  mempunyai hubungan yang kuat terhadap keputusan pembelian. maka dari hasil yang didapat tersebut penulis dapat memberikan beberapa kesimpulan. Kesimpulannya adalah Iklan Media Sosial dan Word of mouth memiliki pengaruh positif dan signifikan terhadap keputusan pembelian.